2009
DOI: 10.1111/j.1365-2656.2009.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of moving versus stationary territorial intruders on territory defence in a songbird

Abstract: Summary1. In territorial contests, not only acoustic or other signals, but also the movements of a territorial intruder are likely to influence the response of a resident. 2. We tested this movement hypothesis by simulating moving vs. stationary intruders into the territories of winter wrens Troglodytes troglodytes, using the same non-interactive song playbacks in both treatments. 3. Male winter wrens showed a different long-term singing reaction in response to a moving than to a stationary intruder. 4. One da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…Overall, our study thus indicates that, in response to temperature, birds shift their acoustic response behaviour to the shorter and simpler alarms, away from songs, the most frequent and supposedly more efficient signal. We assume such a difference in efficiency, because the majority of birds responded to an intruder with singing highlighting the importance of this behaviour in the context of territory defence (Amrhein & Lerch, 2010 Contrary to previous findings, night temperature did not affect the number of songs or calls (Garson & Hunter, 1979;Thomas, 1999). Furthermore, we also expected birds to replenish energetic shortages after colder nights by increasing early-morning foraging, as we have recently demonstrated for this population during winter (Moiron et al, 2018).…”
Section: Temperature Effects On the Acoustic Responsiveness To Intrcontrasting
confidence: 57%
See 1 more Smart Citation
“…Overall, our study thus indicates that, in response to temperature, birds shift their acoustic response behaviour to the shorter and simpler alarms, away from songs, the most frequent and supposedly more efficient signal. We assume such a difference in efficiency, because the majority of birds responded to an intruder with singing highlighting the importance of this behaviour in the context of territory defence (Amrhein & Lerch, 2010 Contrary to previous findings, night temperature did not affect the number of songs or calls (Garson & Hunter, 1979;Thomas, 1999). Furthermore, we also expected birds to replenish energetic shortages after colder nights by increasing early-morning foraging, as we have recently demonstrated for this population during winter (Moiron et al, 2018).…”
Section: Temperature Effects On the Acoustic Responsiveness To Intrcontrasting
confidence: 57%
“…Overall, our study thus indicates that, in response to temperature, birds shift their acoustic response behaviour to the shorter and simpler alarms, away from songs, the most frequent and supposedly more efficient signal. We assume such a difference in efficiency, because the majority of birds responded to an intruder with singing highlighting the importance of this behaviour in the context of territory defence (Amrhein & Lerch, ). Furthermore, our previous work showed that relatively aggressive birds using alarming as a response to intrusions also gain relatively little extra‐pair paternity (Araya‐Ajoy et al, ), implying that alarming has a different signal value, potentially signalling a lack of reserves required for using song as a response.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that spatial movements within [8] as well as across territory boundaries can have strong implications on the behaviour of the resident [7], [34] as well as of neighbours [9]. Other studies showed that also the horizontal location of non-moving rivals within [5] and outside territory boundaries [4], [6] influence territory defence behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Also the location of non-moving rivals within [5] and outside [6] the territory boundaries has been shown to influence territory defence behaviour of residents. Moreover, spatial movements of rivals can affect territorial behaviour of resident males [7], [8] and of neighbours [9], thus highlighting the importance of spatial cues in communication.…”
Section: Introductionmentioning
confidence: 99%
“…), but the capability to adjust territorial defence behaviour to prior experience has only been shown recently in nightingales for particular singing strategies (song overlapping vs. song alternating, Schmidt et al. ) and in a few other songbird species (winter wren: Amrhein & Erne ; Erne & Amrhein ; Amrhein & Lerch ; banded wren: Hall et al. ).…”
Section: Discussionmentioning
confidence: 99%